The Economic Well-being of Farm Households in Germany - Bethge, Sabrina; Wendt, Jost-Frederik; Lakner, Sebastian (German Journal of Agricultural Economics, 2021)
In this study, we explore the economic well-being of farm and nonfarm households in Germany. We applied an indicator that combines households' disposable income and net wealth consisting of financial assets and real estate to data from the Income and Consumption Survey (EVS) 2018. We found that the income available to farm households can support a standard of living equal to that of nonfarm (employed) households. Wealth affects households' economic well-being in both directions: farm households and workers/employees would be better off if their household income would assess their economic status. The opposite trend occurs for unem-ployed and pensioners/retirees. However, the analysis of farmers' well-being requires income data of multiple years regarding the income volatility of self-employment in agriculture. Consid-ering wealth to assess farm households' economic well-being means paying attention to their farm assets because they are highly intertwined with the household. The EVS misses farm char-acteristics and a reliable number of farmers' observations to assess their economic well-being over time to derive agricultural policy implications. Hence, there is currently a lack of statistical data and evidence to achieve the Common Agricultural Policy (CAP) 's second objective to pro-vide income support in a targeted manner.